Karakter Visual Street Furniture Koridor Jalan Diponegoro Kota Surakarta - Wicaksono, Bangkit Adhi (Jurnal Arsitektur Lansekap, 2023)
Visual Characters of Street Furniture Corridor Jalan Diponegoro, Surakarta City. The Surakarta City Government has repaired the Diponegoro Street Corridor because it wants to be like the Malioboro Street Corridor, Yogyakarta City. Repaired objects such as street furniture. Street furniture is an important element in shaping the visual character of the area. This can highlight their identity. This study describes the visual characters that are clearly displayed on the street furniture in the Jalan Diponegoro Corridor, Surakarta City. The indicators used are shape, color, scale, line, rhythm, texture, and proportion and dimensions. The thing to do is to observe, document, and analyze the literature according to the problem. The results of the analysis show that the visual character is dominated by strong square shapes, strong/elegant dark colors, medium scale compared to surrounding objects, simple straight lines, irregularly repeated rhythms, and medium size and good proportions. It is hoped that the explanation above can easily recognize and elevate the identity of the Jalan Diponegoro Corridor area in Surakarta City.